Weight and body composition outcomes with liraglutide in individuals with well-treated hypothyroidism: A retrospective case-control study - Tariq Chukir; Mohammad Yaghmour; Turki Almutairi; Odette Chagoury; Shahrad Taheri (PLoS ONE, 2025)
Background Hypothyroidism is associated with weight gain. Although levothyroxine therapy restores thyroid hormone levels, its impact on weight loss is modest. Whether individuals with appropriately treated hypothyroidism respond differently to obesity pharmacotherapy remains relative unexplored. This study aimed to evaluate weight and body composition responses to liraglutide in patients with obesity and levothyroxine-treated hypothyroidism compared to matched controls without thyroid disease. Methods In this retrospective case-control study, we included adults with overweight or obesity who were treated with liraglutide between 2017 and 2022 at an academic weight management center. Participants with hypothyroidism on stable levothyroxine therapy were compared to age-, gender-, and BMI-matched controls without thyroid disease. Outcomes include percentage weight change, categorical weight loss thresholds and changes in body composition assessed via bioelectrical impedance. Univariate and multivariate regression were used to identify predictors of weight loss. Results Fifty-three patients with hypothyroidism were compared to 145 controls. After a mean follow-up of 10 months, the percent weight change was similar between groups (−10.8% vs. −8.9%, P = 0.940), as was the proportion of weight reduction from fat-free mass loss (29.9% vs. 33.3%, P = 0.729). A significant proportion in both groups achieved ≥5% weight loss (79.2% vs. 71.0%, P = 0.248). Baseline thyroid stimulating hormone (TSH) levels within the normal range did not correlate with weight outcomes. In univariate analysis, baseline metformin use was associated with greater weight loss (P = 0.042), but this was not significant in multivariate models. Conclusion Liraglutide leads to clinically meaningful and comparable weight loss in individuals with well-treated hypothyroidism and those without thyroid disease. Body composition changes were also similar between groups. These findings help clinicians address a frequently asked question among patients with hypothyroidism about their ability to effectively lose weight.